2020
DOI: 10.1007/s13165-020-00294-3
|View full text |Cite
|
Sign up to set email alerts
|

Winter-hardy vs. freeze-killed cover crop mixtures before maize in an organic farming system with reduced soil cultivation

Abstract: The advantages and disadvantages of a winter-hardy vs. a freeze-killed cover crop mixture combined with reduced soil cultivation to a following maize crop were studied on an organic farm in Lower Austria in two consecutive experiments. Effects on soil inorganic nitrogen contents, weed density and the yield of a following maize crop were assessed. The winter-hardy compared with freeze-killed cover crop mixture, both consisting of legumes and non-legumes, reduced soil inorganic nitrogen contents over winter, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…For example, Hashemi et al (2013) showed that NO 3 -N stored in the above-ground biomass of oat decreased by 47% between December and spring of the following year. Similar results were reported by Thorup- Kristensen (1994) who showed for different non-persistent catch crops that after decomposition, between 50% and 80% of previously stored N were lost during winter, resulting in higher N leaching losses in comparison to persistent catch crops (Böldt et al, 2021;Gollner et al, 2020). These losses can significantly reduce nutrient availability to a succeeding crop.…”
Section: 23supporting
confidence: 85%
“…For example, Hashemi et al (2013) showed that NO 3 -N stored in the above-ground biomass of oat decreased by 47% between December and spring of the following year. Similar results were reported by Thorup- Kristensen (1994) who showed for different non-persistent catch crops that after decomposition, between 50% and 80% of previously stored N were lost during winter, resulting in higher N leaching losses in comparison to persistent catch crops (Böldt et al, 2021;Gollner et al, 2020). These losses can significantly reduce nutrient availability to a succeeding crop.…”
Section: 23supporting
confidence: 85%
“…These results highlight that the use of legumes within CC mixtures can increase the risk of N leaching, especially under the maritime climate conditions of Northern Germany, where mild temperatures in autumn promote N release from catch crop residues and high rainfall increase the potential of N losses. Similarly, the use of freeze-killed CC can increase the risk of N leaching, as observed by Gollner et al [19].…”
Section: Introductionmentioning
confidence: 79%
“…The advantage of winter-killed CCs over winter-hardy is the saving of energy for CC termination and the reduction of soil tillage (Gollner et al, 2020). Even no-till practices without herbicide applications are possible if CCs are reliably terminated by frost (Romdhane et al, 2019).…”
Section: Introductionmentioning
confidence: 99%